1977
DOI: 10.4141/cjas77-008
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Value for Beef Steers of Corn Silage as Affected by Harvest Dates and Frost

Abstract: . l9j'7. Feeding value for beef steers of corn silage as affected by harvest dates and frost. Can. J. Anim. An experiment was conducted in 3 consecutive yr with corn grown each year on a field from which silage was made of corn harvested at different dates before and after freezing. Yields of green and dry weight were recorded at each harvest.Individual whole plants and ptant parts were evaluated for dry matter (DM), total nitrogen, total available carbohydrates and in vitro digestibility of DM. Animal gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Similarly, Cartee et al (1994) and Joanning et al (1981) found N digestibility of maize silage with a low DM content (c. 250 g DM kg )1 ) to be significantly higher than that of maize silage containing more than 300 g DM kg )1 . The literature contains other reports of advancing maize maturity having a negative effect on N digestibility (Goering et al, 1969;Calder et al, 1977;St Pierre et al, 1983) although this does not appear to always be the case. Both Colovos et al (1970) and Sutton et al (2000) found no effect of crop maturity on N digestibility over a wide range of silage DM contents (c. 230-390 g DM kg )1 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, Cartee et al (1994) and Joanning et al (1981) found N digestibility of maize silage with a low DM content (c. 250 g DM kg )1 ) to be significantly higher than that of maize silage containing more than 300 g DM kg )1 . The literature contains other reports of advancing maize maturity having a negative effect on N digestibility (Goering et al, 1969;Calder et al, 1977;St Pierre et al, 1983) although this does not appear to always be the case. Both Colovos et al (1970) and Sutton et al (2000) found no effect of crop maturity on N digestibility over a wide range of silage DM contents (c. 230-390 g DM kg )1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The literature contains other reports of advancing maize maturity having a negative effect on N digestibility (Goering et al. , 1969; Calder et al. , 1977; St Pierre et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies from other regions, losses of whole-plant corn dry matter have ranged from 50 to 70% (Lamm and Ward 1981;Willms et al 1993). Losses for whole-plant digestibility during fall (August to mid-October) were minimal, but large losses of stalk and leaves occurred when harvest was delayed into November in New Brunswick (Calder et al 1977).…”
mentioning
confidence: 98%